2008
DOI: 10.1016/j.physleta.2008.03.021
|View full text |Cite
|
Sign up to set email alerts
|

Forces and momenta caused by electromagnetic waves in magnetoelectric media

Abstract: We analyse the propagation of electromagnetic waves in magnetoelectric media. Recently, Feigel has predicted that such a medium may "extract momentum from vacuum" in the sense that the total momentum of the virtual waves (vacuum fluctuations of the electromagnetic field) is nontrivial. Our aim is to check the feasibility of this effect. The crucial point in our study is an assumption of the finite size of the magnetoelectric sample, which allows us to reduce the calculation of the momenta and forces of the ele… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
20
1

Year Published

2008
2008
2011
2011

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 9 publications
(22 citation statements)
references
References 38 publications
1
20
1
Order By: Relevance
“…Further, a new expression for the vacuum stress on the fluid is derived, predicting a Poiseuille flow in a tube, with maximum speed U max ≈ 100µm/s (2000 times larger than Feigel's original estimate of 50nm/s). This prediction contrasts with that of Obukhov & Hehl (2008) that a magnetoelectric slab in the vacuum experiences no net force.…”
Section: Discussioncontrasting
confidence: 71%
See 2 more Smart Citations
“…Further, a new expression for the vacuum stress on the fluid is derived, predicting a Poiseuille flow in a tube, with maximum speed U max ≈ 100µm/s (2000 times larger than Feigel's original estimate of 50nm/s). This prediction contrasts with that of Obukhov & Hehl (2008) that a magnetoelectric slab in the vacuum experiences no net force.…”
Section: Discussioncontrasting
confidence: 71%
“…Turning now to the prediction of Obukhov & Hehl (2008), this implies that a vacuum radiometer, such as the four pane one shown in Fig. 1b, should not turn.…”
Section: Possible Experimental Testsmentioning
confidence: 94%
See 1 more Smart Citation
“…Apart from the vacuum effects in quantum field theory, quantum vacuum in electromagnetic materials can also exhibit some novel effects such as magnetoelectric vacuum birefringence [8], geometric phases at quantum vacuum level [9] and vacuum contribution to medium momentum [10,11] (as far as the vacuum contribution to medium momentum is concerned, Feigel suggested that there is an effect of momentum transfer between quantum vacuum and anisotropic media [10]. Whereas we should also point out that there are some researchers such as van Tiggelen, Rikken [12] and Obukhov, Hehl [13] who have contested the conclusion of Feigel). These vacuum effects are the phenomena taking place in the materials at rest, and, to the best of our knowledge, less attention was paid to the vacuum effects inside moving materials.…”
Section: Introductionmentioning
confidence: 93%
“…Since the quantum vacuum would have a nonzero momentum, one can conjecture that this would therefore lead to the effect of transfer of some dynamical physical quantities (such as momentum, energy, and even angular momentum) between the quantum vacuum and the moving material. In the reference [10], Feigel has considered the problem of quantum vacuum contribution to the medium momentum, where he suggested that the momentum transfer between a magnetoelectric medium and the quantum vacuum can possibly take place (though some researchers [12,13] have contested the conclusion of Feigel). As there is also a magnetoelectric coupling in the constitutive relation of the moving medium, we expect that such a quantum-vacuum mechanical effect would also emerge from the present system (the moving medium and the anisotropic vacuum).…”
Section: Nonzero Momentum Density Of Anisotropic Quantum Vacuummentioning
confidence: 99%